Investigating the Integration of IoT Devices and Data Analytics for Efficient Management in Oil and Gas Exploration and Production Facilities - Idris, Zago Salisu; Abdu, Khalid Fatima; Binni, Muhammad Amina (Darul Yasin Al Sys, 2025)
As the global energy landscape evolves, the oil and gas industry is undergoing a significant transformation in response to growing demands for sustainability, operational efficiency, and reduced environmental impact. Encompassing the exploration, extraction, refining, and distribution of petroleum and natural gas, the sector remains a critical economic driver while contending with volatile market dynamics, geopolitical pressures, and increasingly stringent environmental regulations. Emerging technologies such as the Internet of Things (IoT), big data analytics, and artificial intelligence (AI) are being deployed to optimize energy usage, improve operational efficiency, and lower emissions. Innovations including real-time monitoring and predictive maintenance are contributing to cost reduction and a decreased environmental footprint. While the industry plays a pivotal role in meeting global energy needs, it faces mounting pressure to transition toward cleaner energy solutions. Many companies are investing in renewable energy sources and carbon capture technologies to align with international decarbonization targets. Nevertheless, the shift presents substantial challenges, including high capital investment requirements, infrastructure limitations, and cybersecurity risks associated with digitalization. These complexities underscore the industry's ongoing struggle to balance economic viability with environmental responsibility.